Gender differences, environmental pressures, tumor characteristics, and death rate in a lung cancer cohort: a seven-years Bayesian survival analysis using cancer registry data from a contaminated area in Italy - Mincuzzi, Antonia; Carone, Simona; Galluzzo, Claudia; Tanzarella, Margherita; Lagravinese, Giovanna Maria; Bruni, Antonella; Rashid, Ivan; Bisceglia, Lucia; Sardone, Rodolfo; Addabbo, Francesco; Minerba, Sante; Giannico, Orazio Valerio (Frontiers in Public Health, 2024)
In Taranto, Southern Italy, adverse impacts on environment and human health due to industrial installations have been studied. In literature, associations were reported between gender, environmental factors and mortality in men and women with lung cancer. The aim of this study was to investigate the relationships between gender, residence in areas with high environmental pressures, bronchus/lung cancer characteristics and death rate. Data from the Taranto Cancer Registry were used, including all men and women with invasive bronchus/lung cancer diagnosed between 01/01/2016 and 31/12/2020 and with follow-up to 31/12/2022. Bayesian mixed-effects logistic and Cox regression models were fitted with the approach of Integrated Nested Laplace Approximations, adjusting for patients and disease characteristics. A total of 2535 person-years were observed. Male gender was associated with higher prevalence of histological grade 3 (OR 2.45,) and lung squamous-cell carcinoma (OR 3.04, 95%CrI 1.97-4.69). Variables associated with higher death rate were male gender (HR 1.24, 95% CrI 1.07-1.43), pathological/clinical stage II (HR 2.49, 95%CrI 1.63-3.79), III (HR 3.40, 95%CrI 2.33-4.97) and IV (HR 8.21,, grade 3 (HR 1.80, 95%CrI 1.25-2.59), lung squamouscell carcinoma (HR 1.18, 95%CrI 1.00-1.39) and small-cell lung cancer (HR 1.62, 95%CrI 1.31-1.99); variables associated with lower death rate were other-type lung cancer (HR 0.65, 95%CrI 0.44-0.95), high immune checkpoint ligand expression (HR 0.75, 95%CrI 0.59-0.95), lung (HR 0.73, 95%CrI 0.62-0.86) and left localization (HR 0.85, 95%CrI 0.75-0.95). The results didn't show a clear association between residence in the SIN and prevalence of the above-mentioned prognostic factors as well as between residence in the SIN and death rate. The results findings confirmed the independent prognostic values of different lung cancer characteristics. Even adjusting for patients and tumor characteristics, male gender seemed to be associated with higher prevalence of poorly differentiated cancer and squamous cell carcinoma, and with an increased death rate.